Youth Entrepreneurship - Challenges In Kerala - Aneesha P Chellappan (REVIEW OF SOCIAL SCIENCES, 2018)
Entrepreneurship is the attempt to create value through recognition of business opportunity, the management of risk taking appropriate to the opportunity and through the communicative and management skill to mobilize human, financial, managerial and material resources necessary to bring project to function. Hence it needs professional application of knowledge, skills and competencies to start an enterprise or diversifying from an existing one. Youth is considered to be the future of every nation. Youth is the stage of life when a person has dreams and hopes. They have high aspirations and energy. In the present scenario business creation and development of entrepreneurial culture are the alternatives for the youth since they face the problem of unemployment and under employment. The young people face challenges in connection with setting up of their enterprises. They can develop only through various support systems by the supportive environment. The present study tries to analyses the major difficulties faced by the youth to start up their venture.